Monitoring Infus Dan Detak Jantung Berbasis Internet Of Things (IoT) - M Syafiih; Nadiyah Nadiyah; Sri Astutik Andayani; Nur Hatima Inda Arifin (Jurnal Ilmiah Informatika, 2023)
An alternative medical device called an IV is used to replenish lost body fluids and maintain the body's electrolyte balance. Infusion fluid administration is a very useful way to help and speed up the recovery of the patient's condition during the treatment period. In hospitals, clinics and health centers, nurses generally still control and monitor the use of IV fluids manually. Nurses must periodically check the condition of each patient's infusion. Thus, delays in infusion replacement often occur. This has a negative impact on the patient, such as blood being sucked into the infusion hose and the possibility of clotting in the hose. So that patients will experience losses to these conditions, nurses are required to always be on time in replacing infusions. There are still many people who do not understand the normal human heart rate, because health workers do not socialize to the public about heart rate. Lack of understanding of the human heartbeat that is often found in our environment. Based on the above problems, the research to be carried out will provide several solutions, it is necessary to make a sensor to detect infusion filling for patients who are under treatment so that it will help nurses in controlling infusion filling. The existence of monitor results related to human heart rate as a tool so that it can measure human heart rate. The method used is Rapid Application Development (RAD), this research produces a sensor tool to detect infusion and human heart rate.